Implementasi Peradilan Anak yang Berhadapan dengan Hukum pada Tahap Adjudikasi yang Berbasis HAM - Firdaus Firdaus (Badan Strategi Kebijakan Hukum, 2013)
Rights of children in conflict with the law which consists of the right to be examined in a family, the right to always be accompanied by a parent / guardian or foster parent, the right to be accompanied by a supervising community and the right to be accompanied by legal counsel can not be protected and enforced. While the factors that support and hinder the implementation process of children in conflict with the law are based on the ignorance of the rights of children suspected or accused child rights are protected by laws and regulations, law enforcement officials are not divulging information about rights owned by the suspect or the accused child either intentionally or unintentionally, there is no provision that expressly regulate the legal consequences if the rights of the suspect or defendant is not notified or violated and the role of legal counsel in the examination of cases of children in conflict with the law in the District Court of the less obvious